Diospyros xylocarpa, a New Species of Ebenaceae from China and Vietnam - Sima, Yong-Kang; Chen, Wen-Hong; Wu, Jian-Yong; Shui, Yu-Min (Phytotaxa, 2021)
A new species of Ebenaceae, Diospyros xylocarpa Y. M. Shui, W. H. Chen & Sima, from China and Vietnam, is described and illustrated. The new species is similar to D. phuketensis Phengklai, but differs in its bigger and densely ochre brown villous leaves, more pairs of lateral veins, shorter petioles, 8-locular ovaries, xyloid fruits with nearly square fruiting calyx and much shorter fruiting peduncle and eight seeds. The new species is also similar to D. dasyphylla Kurz, but differs in its leaf blades with a cuneate to round base, eight stamens and bigger and xyloid fruits.